SOCIAL AND DEMOGRAPHIC FACTORS OF PHYSICAL ACTIVITY IN 9-11 YEARS OLD SLOVENIAN CHILDREN (Kinesiology, 2018)
Factors related to physical behaviour of children are important in understanding the characteristics of their physical activity. Apart from the factors of physical environment, social and demographical factors are also related to physical activity levels. Randomly selected 669 children (9.9±0.8 years; 48.8% boys) from randomly selected Slovenian elementary schools participated in this study. All data were obtained during a single measurement in May 2010. The standardized questionnaire The Quality of Life Survey was used to measure physical activity (PA) levels as well as social and demographic factors which could be associated with it. The results indicated higher PA levels in boys than in girls (704±286 min/week vs. 617±268 min/week; p